Practical Japanese cooking : - Tsuji, Shizuo (Kodansha International, 1986)
The book presents over 100 authentic recipes (manageable even for the novice cook) for dishes ranging from familiar favorites like Miso Soup with Pork and Vegetables, Yakitori, Rice Balls, Nigiri Sushi, Soba Noodles in a Basket, Sukiyaki, and Tempura to more exotic-sounding (but actually simple to prepare) fare such as Jade Green Deep-Fried Shrimp, Yellowtail Teriyaki, Paper-Thin Sea Bass Sashimi, Sake-Simmered Lobster, Nagasaki-Style Braised Pork, Simmered Tofu Dumplings, and Turnip with Ginger-Miso Sauce. Full-color photos showcase the finished dishes and illustrate the steps involved in their preparation. Tsuji also explains many of the techniques used; and here, again, detailed photos clarify the instructions.